Realizing an Epitaxial Decorated Stanene with an Insulating Bandgap. (1st July 2018) - Zang, Yunyi; Jiang, Tian; Gong, Yan; Guan, Zhaoyong; Liu, Chong; Liao, Menghan; Zhu, Kejing; Li, Zhe; Wang, Lili; Li, Wei; Song, Canli; Zhang, Ding; et al.
Abstract: The exploration of intriguing topological quantum physics in stanene has attracted enormous interest but is challenged by lacking desirable material samples. The successful fabrication of monolayer stanene on PbTe(111) films with low‐temperature molecular beam epitaxy and thorough characterizations of its atomic and electronic structures are reported here. In situ angle‐resolved photoemission spectroscopy together with first‐principles calculations identify two hole bands of p xy orbital with a spin‐orbit coupling induced band splitting and meanwhile reveal an automatic passivation of p z orbital of stanene. Importantly, material properties are tuned by substrate engineering, realizing a decorated stanene sample with truly insulating bulk on Sr‐doped PbTe. This finding paves a road for studies of stanene‐based topological quantum effects and electronics. Abstract : Single‐layer stanene epitaxied on PbTe(111) film is fabricated by low‐temperature molecular beam epitaxy . The characteristic band structure of stanene around the bulk gap is observed by angle‐resolved photoemission spectroscopy. Stanene samples with a full bulk gap are realized by Sr‐doping‐induced enhancement of PbTe bandgap, which paves the road for studies of stanene‐based topological quantum effects and electronics.